Diversification and Size on U.S. Bank Holding Companies and Commercial Banks : are big banks too big to fail? - Cunha, Miguel Ângelo Gomes da (2020)
The present Dissertation’s academic research question addresses the impact that diversification and size have on the financial stability of U.S. Bank Holding Companies (BHCs) and Commercial Banks for the 2002-2016 period. The bank yearly data was extracted from OSIRIS-Bureau van Dijk, while the macro variables were extracted from the Trading Economics website. In order to address the proposed research question, a baseline model, consisting on a random effects model including time fixed effects and clusters, was created with the dependent variables being the standard deviation of ROA and the Distance-to-Default, both serving as proxies for banks’ financial stability. Furthermore, the present Dissertation controls for the time periods before, during and after the U.S. Subprime Financial Crisis. In general, the findings confirm that appropriate levels of diversification improve the financial stability of BHCs and Commercial Banks, however, after a given threshold diversification deteriorates banks’ financial stability. Moreover, it is also confirmed that increases in the size of Commercial Banks lead to increases in banks’ financial stability, nonetheless, after a given threshold further increases in size deteriorates banks’ financial stability. Surprisingly, concerning BHCs, increases in size lead to decreases in banks’ financial stability, while, after a given threshold, further increases in size promote banks’ financial stability. The present Dissertation looks at this last relationship as a possible confirmation of the “Too-Big-to-Fail” issue, that may have risen from the U.S. Subprime Financial Crisis. Lastly, robustness analysis conducted confirm the previous findings.